MiR-495 Inhibits Cisplatin Resistance and Angiogenesis in Esophageal Cancer by Targeting ATP7A. (November 2021) - Li, Zhuanghua; Li, Shaowen; Wen, Yongqin; Chen, Jingtang; Liu, Kejun; Jia, Jun
Background: Cancer resistance to chemotherapy is closely associated with changes in transporter systems. In this study, we investigated the possible regulation of 1 copper ion transporter (ATP7A; ATPase copper transporting alpha) by microRNA miR-495 and its implications in cisplatin resistance and angiogenesis in esophageal cancer.Methods: MiR-495 and ATP7A mRNA expression in clinical tissue samples and 2 cancer cell lines (Eca-109 and TE1) were detected by quantitative real-time polymerase chain reaction. The levels of miR-495 and ATP7A expression in Eca-109 and TE1 cells were increased by transfection with miR-495 mimics and ATP7A-overexpression vectors. Cell proliferation, apoptosis, and angiogenesis were assessed by CCK-8, flow cytometry, and tube formation assays, respectively. The levels of TNF-α and VEGF in cell culture supernatants were detected by enzyme linked immunosorbent assay, and in situ expression of NLRP3 was measured by immunofluorescence. The binding of miR-495 to ATP7A sequences was verified by dual luciferase reporter assays.Results: ATP7A expression was significantly increased, while miR-495 expression was decreased in the cancer tissues of esophageal cancer patients. MiR-495 mimics decreased the proliferation and promoted the apoptosis of cisplatin-resistant Eca-109 and TE1 cells. Furthermore, tube formation by human umbilical vein endothelial cells, TNF-α and VEGF secretion, and the levels of MRP1, ABCG1, ABCA1, and NLRP3 expression in cisplatin-resistant Eca-109 and TE1 cells were all reduced by miR-495 mimics. MiR-495 was shown to directly bind to ATP7A gene sequences to repress ATP7A expression in Eca-109 and TE1 cells. ATP7A overexpression substantially abrogated the changes in proliferation, apoptosis, angiogenesis, and above-mentioned gene expression in cisplatin-resistant Eca-109 and TE1 cells.Conclusions: MiR-495 suppressed cisplatin resistance and angiogenesis in esophageal cancer cells by targeting ATP7A gene expression.